Analysis of free vibrations of sandwich panel with electrorheological layer based on two models of laminated shells - Mikhasev, Gennadi I.; Botogova, Marina G.; Mikhievich, Arnold P. (Journal of the Belarusian State University. Mathematics and Informatics, 2020)
Based on two models of laminated shells, free low frequency vibrations of a three-layered cylindrical panel with the internal layer fabricated of an electrorheological composite are studied. Both models lead to the same governing equations accounting for shears in layers, but differ in equations for calculating the reduced shear parameter which depends on the electric field strength and the temperature of a composite. In the case of a simple support of all edges, the formula for the complex natural frequency is obtained explicitly. The influence of the electric field strength and the temperature of the electrorheological composite on the lowest natural frequencies and associated vibration decrements is investigated. It was detected that both models give very close results for the heated composite at an electric field strength of more than 1.5 kV/mm. It is also shown that the frequency of natural vibrations of the electrorheological panel is a monotonically increasing function of the electric field strength, while the decrement – strength curve shows the presence of a local maximum corresponding to the best damping of viscoelastic vibrations.
Keywords: sandwich panel; electrorheological composite; natural frequencies; decrement of vibrations